153 Clinical auditing as an instrument to improve cancer care: the dutch gynaecological oncology audit (DGOA). (13th November 2020) - Tewarie, N; Wouters, M; Van Driel, W; Kruitwagen, R
Abstract : Introduction: The Dutch Gynaecological Oncology Audit (DGOA) was initiated in 2013 where all patients with a gynaecological malignancy are registered. The aim of this study is to present the first results of clinical auditing from the DGOA for ovarian-, cervical-, endometrial- and vulvar cancer. Methods: The DGOA is facilitated by the Dutch Institute of Clinical Auditing and run by its own scientific committee. Items are collected through a web-based registration based on a set of quality indicators. Results are frequently updated and benchmarked information is given back to the user. Data verification was done in 2016 where the accuracy and completeness was checked. Results: Between 01 January 2014 and 31 December 2018, a total of nearly 18.000 patients were registered. Case ascertainment was 98.3% in 2016. Percentage of patients with ovarian cancer waiting less than 28 days to start with any form of therapy decreased over time from 57.3% in 2014 to 40.9% in 2018 (p<0.001).The percentage of patients who underwent primary cytoreductive surgery (CRS) also decreased over time (57.8% – 39.7%, P<0.001), patients with complete primary CRS improved (53.5%-69.1%, P<0.001, ( figure1)). Other measured quality indicators did not significantly change over time. Conclusion: The DGOA provides valuable data on the quality of care for patients diagnosed with a gynaecological malignancy. Data shows variation between hospitals with regard to pre-determined quality indicators. The results of the so called 'best practices' are shared with participants of the clinical audit with the aim of improving quality of care in the Netherlands.